Two doors to landscapes of the end of the world in the contemporary scene of Ceará (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article discusses some aspects associated with the idea of ​​the end of the world to approach the landscapes created by two contemporary stagings produced in the state of Ceará. The shows Pra Frente o Pior (2016) by Inquieta CIA – colective direction and Paraíso (2019) by Teatro Máquina – directed by Fran Teixeira are approached in the light of propositions by authors such as Déborah Danowski and Eduardo Viveiros de Castro (2017), Ailton Krenak (2020), Eleonora Fabião (2013), Alexandre Dal Farra Martins (2018), among others. The reflective journey undertaken configures two doors, associated with the notions of Anthropocene and cheerful pessimism, as possible contributions to the analysis of scenic creations interested in the poetic articulations of the end.
Keywords: Brazilian theater; Theater from Ceará; Anthropocene; Cheerful pessimism; Landscape